Expressão dos genes PCA3 e PSA e sua utilização como marcadores no diagnóstico do câncer prostático e hiperplasia benigna da próstata - Fernanda Fonseca Coelho (2014)
Prostate cancer (PCa) is the second most common cancer in men worldwide. Due to the increased number of cases, it is important to develop a non-invasive test for the differential diagnosis of PCa and other prostatic alterations. Studies have shown that the gene 3 of prostate cancer (PCA3) shows high levels of expression in tumor tissue, which would be associated with increased probability of a positive biopsy. This study evaluated the expression of PCA3 and PSA genes in urine from patients with nodular prostatic hyperplasia (BPH) or PCa adenocarcinoma type, compared to a group of healthy individuals. The study included 59 men treated at the Clinical Hospital of the Federal University of Minas Gerais (HC-UFMG) to perform prostate biopsy, 22 patients with PCa, 26 BPH and 11 healthy subjects (controls). Post-prostatic massage urine was collected which the RNA was obtained. Real Time PCR performed the absolute quantification of the PCA3 and PSA genes expression. In addition, we obtained the values of total serum PSA. Among subjects with detection of PCA3 expression, 16 presented positive biopsy and only 4 had negative biopsy. Among subjects with BPH, 4 showed detectable levels of PCA3, while in the control group, no individual revealed detection of this gene expression. No significant difference was observed in the mean number of copies of PCA3 and PSA genes, PCA3/PSA ratio and total PSA levels when the groups of patients with PCa and BPH were compared, but a higher number of individuals with CaP and positive expression of PCA3 and PSA and total PSA levels 4ng/mL was observed when compared to the other groups. The area under the ROC curve was 0.625; 0.596; 0.559 and 0.503, respectively for the variables mentioned above. The sensitivity and specificity of the PCA3 test were 73% and 85%, respectively. Considering the estimated cutoff values (0.2219 and 0.5007 for the PCA3 and PCA3/PSA relation), we observed a significant difference between the number of individuals with values above these in PCa group compared to the BPH. We conclude that the qualitative expression of PCA3 test could be applied in the initial screening for differentiation of the individual with CaP or BPH from those without prostate changes. However, the quantitative test for the PCA3 and PSA number of copies was not able to discriminate individuals with CaP or BPH, and further studies with a larger sample group should be conducted in order to confirm these findings.